2005
DOI: 10.1093/bioinformatics/bti258
|View full text |Cite
|
Sign up to set email alerts
|

Robust estimation of protein expression ratios with lysate microarray technology

Abstract: http://www.cs.tut.fi/~mirceanc/lysate_array_bioinformatics.htm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…BSA has numerous biochemical applications, including protein microarray technology [3], lysate microarray technology [4], enzyme-linked immunosorbent assay (ELISA) [5,6], immunoblots as a blocking agent during western blotting to reduce background and non-specific binding [7], and immunohistochemistry [8]. Moreover, it is generally used in vaccine delivery studies as a model protein [9][10][11][12][13][14], owing to its ease of assay, well-known immunogenicity pattern, well-known physicochemical properties, low cost, and general availability.…”
Section: Introductionmentioning
confidence: 99%
“…BSA has numerous biochemical applications, including protein microarray technology [3], lysate microarray technology [4], enzyme-linked immunosorbent assay (ELISA) [5,6], immunoblots as a blocking agent during western blotting to reduce background and non-specific binding [7], and immunohistochemistry [8]. Moreover, it is generally used in vaccine delivery studies as a model protein [9][10][11][12][13][14], owing to its ease of assay, well-known immunogenicity pattern, well-known physicochemical properties, low cost, and general availability.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a universal reference standard on each RPPM has been suggested as one solution to compensate for the variability introduced by different instruments and experimental factors (Sheehan et al, 2005). Data analysis of RPPMs, especially those with serial sample dilutions, is somewhat more complex than in DNA microarrays (Mircean et al, 2005). As in ELISA applications, standard curves must be generated for each antibody.…”
Section: Challenges Of Rppmsmentioning
confidence: 99%
“…Mapping in vitro phosphoprotein signaling pathways using RPMA RPMA has demonstrated the sensitivity necessary to distinguish protein expression ratios of low abundance protein species in whole cell lysates and in rare cell populations [25, 100,105,[125][126][127]. Wei et al recently utilized RPMA to evaluate nucleotide excision repair (NER) proteins in lymphocyte cell lines derived from patients with newly diagnosed squamous cell carcinomas of the head and neck (SCCHN), and compared these protein expression levels to those of clinically matched normal controls [126,127].…”
Section: Analytical Challengesmentioning
confidence: 99%
“…Wei et al recently utilized RPMA to evaluate nucleotide excision repair (NER) proteins in lymphocyte cell lines derived from patients with newly diagnosed squamous cell carcinomas of the head and neck (SCCHN), and compared these protein expression levels to those of clinically matched normal controls [126,127]. When NER protein levels were stimulated by transfection with damaged and undamaged plasmid DNA, it was found that lymphocytes derived from SCCHN patients had significantly lower overall levels of NER protein expression, suggesting that SCCHN maintain a higher tolerance to DNA damage.…”
Section: Analytical Challengesmentioning
confidence: 99%